New Self‐Organization Route to Tunable Narrowband Optical Filters and Polarizers Demonstrated with ZnO–ZnWO4 Eutectic Composite. Issue 7 (10th January 2020) - Osewski, Paweł; Belardini, Alessandro; Centini, Marco; Valagiannopoulos, Constantinos; Leahu, Grigore; Li Voti, Roberto; Tomczyk, Monika; Alù, Andrea; Pawlak, Dorota A.; Sibilia, Concita
Abstract: Electromagnetic fields interacting with microscopic structural features in a composite material provide emerging optical properties that surpass those offered by the individual components. However, composite materials can be generally lossy due to the scattering effects induced by inhomogeneities at the interfaces between different compounds. To overcome such problems, complicated and costly manufacturing procedures, such as top‐down approaches, are generally required. In contrast, here ZnO–ZnWO4 eutectic self‐organized composites grown by the micropulling method are considered, displaying sharp and strongly polarized transmission at 397 nm. Such an optical response is notable because it is not observed in either ZnO or ZnWO4 single crystals. The optical response is due to the refractive index matching of the two constituents, which self‐organize into ordered structures via a micropulling down method. The optical behavior reported here can directly lead to applications, such as tunable narrowband filters with bandpass of 3 nm and polarizers, paving the way to a new self‐organization route for manufacturing optical components. Abstract : A new ZnO–ZnWO4 eutectic composite manifests sharp and strongly polarization‐dependent transmission at ≈400 nm. Such a powerful effect is due to the formation of a fine self‐organized eutectic nano/microstructure that enables refractive index matching. These functionalities are obtained by fabricating ZnO–ZnWO4 using a self‐organization low‐cost procedure, paving the way for large‐scale applications, such as tunable narrowband color filters.